Progress Report on the Activities of the Independent Evaluation Office (IEO). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Since its last Report to the IMFC in Singapore, the IEO has focused most of its attention on completion of two evaluations; namely the IMF and Aid to Sub-Saharan Africa and the IMF's Advice on Exchange Rate Policy. In addition work is progressing or has been initiated on a number of new topics identified in the last Report.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Evaluation; IEO Report; IEO Work Program; Policy; PP; Singapore